2003
DOI: 10.1161/01.hyp.0000047103.07205.03
|View full text |Cite|
|
Sign up to set email alerts
|

Microarray Analysis of Rat Chromosome 2 Congenic Strains

Abstract: Abstract-Human essential hypertension is a complex polygenic trait with underlying genetic components that remain unknown. The stroke-prone spontaneously hypertensive rat (SHRSP) is a model of human essential hypertension, and a number of reproducible blood pressure regulation quantitative trait loci have been found to map to rat chromosome 2. The SP.WKYGla2c* congenic strain was produced by introgressing a region of rat chromosome 2 from the normotensive Wistar Kyoto (WKY) strain into the genetic background o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 43 publications
3
66
0
Order By: Relevance
“…Amongst the classes of GST enzymes the mu class is particularly involved in detoxification of free radicals. GSTM enzymes protect against oxidative stress, and or reduced expression of Gstm1 has been found to be associated with hypertension in rats [23,34,35]. This text box shows major mechanisms but is by no means a comprehensive overview of the pathogenesis of hypertension.…”
Section: Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst the classes of GST enzymes the mu class is particularly involved in detoxification of free radicals. GSTM enzymes protect against oxidative stress, and or reduced expression of Gstm1 has been found to be associated with hypertension in rats [23,34,35]. This text box shows major mechanisms but is by no means a comprehensive overview of the pathogenesis of hypertension.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…First, WTCCC was the first large-scale genome 24 scan using dense SNP markers across the genome. Previous genome scans were limited by the 25 in SHRSP and chromosome 2 congenic strains [34,35], GSTM genes were subject to association 1 studies in humans [39][40][41] due to the fundamental role of the oxidative stress pathway in 2 cardiovascular pathophysiology [42,43]. While there is agreement on the involvement of genetic 3 variants of GSTMs in the development of cancer [44,45], studies on the role of GSTMs in 4 cardiovascular diseases are less consistent [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…The search for differential gene expression has recently received considerable attention as a means of finding candidate genes for QTLs (Liang et al, 2003;McBride et al, 2003;Moujahidine et al, 2004;Garrett et al, 2005;Hubner et al, 2005;Yagil et al, 2005). It is easy to understand the tantalizing appeal of such an approach, because it generates gene candidates directly, rapidly and immediately, with apparent performance differentials.…”
Section: Use Of Heterozygotes As a Deductive Functional Test Of Qtlsmentioning
confidence: 99%
“…Only a few microarray analyses of the SHR have been published, evaluating adipose tissue, 44 kidney, 45,46 and vascular smooth muscle cells. 47 The adipose tissue study, performed by Aitman et al, 44 was a landmark experiment because microarray data were used to pinpoint the Cd36 gene (fatty acid translocase) as a genetic underpinning of insulin resistance, defective fatty acid metabolism, and hypertriglyceridemia in the SHR.…”
Section: Perspectivesmentioning
confidence: 99%
“…Furthermore, such rat studies usually did not present data on the same genes that we found differentially expressed. A study of chromosome 2 congenic kidneys 45 did, however, find a significant reduction of glutathione S-transferase 2 (Gstm2), a gene involved in the oxidative stress response, and mapped this gene through comparative genome analysis to corresponding regions on rat chromosome 2, mouse chromosome 3, and human chromosome 1. RT-PCR investigation of the adrenal gland of the SHR found a statistically significant 2.5-fold increase of tyrosine hydroxylase expression in the SHR as compared with its normotensive control, the Wistar-Kyoto rat.…”
Section: Perspectivesmentioning
confidence: 99%